Death at a funeral [videorecording (DVD)] - Oz, Frank; Macfadyen, Matthew, 1974-; Hawes, Keeley, 1976-; Nyman, Andy (20th Century Fox Home Entertainment, 2008)
Daniel is a decent young man who is married to Jane. They live at his father's home. When his father dies, it his up to him to organize his funeral. On the morning of the funeral, with a suitably grave expression on his face, Daniel is ready to welcome his father's friends and relatives. But preserving the dignity inherent in such a circumstance will be a hard task. Particularly with an undertaker who botches his work. His famous, but selfish brother has returned from the USA. His cousin's fiancé has accidentally ingested drugs. A man takes advantage of the sad event to win back the heart, or rather the body, of a woman who is about to marry another. A handicapped old uncle who is also the most unbearable pain in the neck. To cap it all, Daniel notices the presence among the mourners of a mysterious dwarf nobody else seems to know.